Synergistic effects of multi-strain probiotics and Chinese herbal medicine on growth performance and gut health in weaned piglets - Ji, Kai; Lei, Sheng; Wang, Lingling; Tian, Lang; Wen, Zizeng; Shi, Rongjing; Liu, Lin; Liu, Jinjia; Shi, Baoming; Wang, Jian (Frontiers in Veterinary Science, 2025)
BackgroundWeaning stress represents a considerable challenge in global swine production. While probiotics and Chinese herbal medicine have been extensively studied as individual interventions, their combined application as alternative feed additives in swine production requires further investigation.MethodsForty-five weaned piglets (35 ± 3 days old) were randomly allocated to five treatment groups (n = 9 per group) for a 28-day feeding trial: control (CON), antibiotic (A), probiotic (PRO), Chinese herbal medicine (CHM), and probiotic plus Chinese herbal medicine (PROC). Growth performance, serum antioxidant levels, and immune parameters were assessed alongside 16S rRNA microbiome sequencing and liquid chromatography-mass spectrometry metabolomics analysis.ResultsThe PROC group significantly improved growth performance compared to controls (p < 0.05), showing 8.91% higher final body weight, significantly increased average daily gain, and the most efficient feed conversion ratio (1.55) among treatments. Serum analysis indicated a significant increase in total antioxidant capacity (T-AOC) in the PROC group relative to the other groups. The probiotic (PRO) and PROC groups enhanced superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities, while reducing malondialdehyde (MDA) levels (p < 0.05). Pro-inflammatory cytokines IL-2 and IL-6 were significantly reduced in the PRO and PROC groups, while immunoglobulins IgA and IgG levels were increased (p < 0.05). Microbiota analysis revealed increased α-diversity (Shannon and Chao1 indices) and altered community structure in the PROC group. Metabolomic profiling identified 5,090 metabolites with distinct profiles between groups based on OPLS-DA. KEGG pathway analysis indicated that the PRO group exhibited enrichment in nucleotide and purine metabolism, whereas the PROC group activated supplementary pathways, including purine and lipid metabolism.ConclusionThese findings suggest that combined probiotic and Chinese herbal medicine supplementation may serve as an effective feed strategy for promoting intestinal health and alleviating weaning stress, providing valuable insights for developing antibiotic alternatives in swine production.